Age of Partner at First Adolescent Intercourse and Adult Sexual Risk Behavior Among Women - Senn, Theresa E. (Mary Ann Liebert, Inc., 2011)
BACKGROUND: Adolescent females who have early sexual experiences with older male partners report high rates of sexual risk behavior during adolescence, but little is known about whether these early sexual experiences are associated with adult sexual risk behavior. The purpose of this study was to investigate whether having first consensual sex with an older partner was associated with sexual risk behavior in adulthood. METHODS: Participants were 292 women (66% African American, mean age = 26 years) attending a public sexually transmitted disease (STD) clinic who reported having voluntary vaginal sex before age 18. Participants completed a computerized survey assessing child/adolescent sexual experiences and current adult sexual risk behavior. RESULTS: Participants were, on average, 14.6 years at first vaginal intercourse; their partners were, on average, 17.5 years. After controlling for covariates, a greater partner age difference at first intercourse was associated with more episodes of unprotected sex with a steady partner and a greater proportion of episodes of unprotected sex with a steady partner in the past 3 months. CONCLUSIONS: Having an older first sex partner during adolescence was associated with sexual risk behavior in adulthood. Early sexual experiences may be important life events that influence subsequent sexual behavior. Sexual health interventions need to target female adolescents before they initiate sexual intercourse to reduce risk for STDs and human immunodeficiency virus (HIV) infection.